Surface Defect Detection Algorithm for Wind Turbine Blades Based on HSCA-YOLOv7 - Bing LI; Yunshan BAI; Kuan ZHAO; Congbin GUO; Yongjie ZHAI (Zhongguo dianli)
The blade is one of the key components of the wind turbine, which is vulnerable to the impact of natural environmental factors, resulting in gel coat falling off, cracks, corrosion, and other damage and thus affecting the efficiency of wind power generation and the safety of wind turbine operation. A defect detection algorithm for wind turbine blades based on HSCA-YOLOv7 is proposed to address the issues of inconsistent defect scale, inaccurate positioning, and low detection accuracy in wind turbine blade images by aerial photography. Firstly, based on the images of wind turbine blades collected by drones, a dataset of blades is created, and Mosaic and MixUp methods are used for data amplification. Then, deep separable convolutions with different expansion rates are introduced into the improved spatial pyramid pooling (ISPP) module to reduce the loss of details caused by pooling operations. Hybrid spatial channel attention (HSCA) is proposed to capture the global visual scene context, increase the semantic difference between target features and the environment, and solve the problem of inconsistent defect scales in blade images. The focal EIoU loss function is used to solve the problem that the length and width of the prediction box are wrongly amplified and improve the positioning ability of the model for blade defects. The experimental results show that the mAP and mAR of the proposed algorithm reach 83.64% and 71.96%, respectively, which are 3.37% and 5% higher than the YOLOv7 baseline algorithm.